Small Estates (Distribution) Act 1955: analysis on the 2022 amendment and its effects over the inheritance management - Drs Nasrul, Muhammad Amrullah (IIUM Press, 2023)
This study aims to analyse the amendments to the Small Estates(Distribution) Act 1955 by looking at each amendment and identifying its impact on other relevant administrative bodies. This qualitative study involved library-based research in which the authors reviewed relevant literature for the purpose of data collection, namely newspapers, textbooks, conference proceedings, case laws, seminar papers, and journal articles. The amendment shows some overlap with the jurisdiction of other administrative bodies, specifically the Amanah Raya Berhad (ARB). The paper suggested that further amendments be made to other administrative bodies, namely the Civil High Court and ARB in order to prevent such overlapping.